2017
DOI: 10.1186/s40168-017-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, spatial, and maternal effects on gut microbiome in wild red squirrels

Abstract: BackgroundOur understanding of gut microbiota has been limited primarily to findings from human and laboratory animals, but what shapes the gut microbiota in nature remains largely unknown. To fill this gap, we conducted a comprehensive study of gut microbiota of a well-studied North American red squirrel (Tamiasciurus hudsonicus) population. Red squirrels are territorial, solitary, and live in a highly seasonal environment and therefore represent a very attractive system to study factors that drive the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
204
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(216 citation statements)
references
References 73 publications
11
204
1
Order By: Relevance
“…Additionally, we observed cyclic behavior of biomass trajectories in multiple individuals, similar to the seasonal patterns reported in hunter-gatherers of western Tanzania 57 , and the evolutionarily conserved patterns observed in other mammals 58 . Similar patterns have not been reported before for western city dwellers, perhaps due to the confounding effects of aggregate analysis across individuals and the impact of highly diverse diets.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, we observed cyclic behavior of biomass trajectories in multiple individuals, similar to the seasonal patterns reported in hunter-gatherers of western Tanzania 57 , and the evolutionarily conserved patterns observed in other mammals 58 . Similar patterns have not been reported before for western city dwellers, perhaps due to the confounding effects of aggregate analysis across individuals and the impact of highly diverse diets.…”
Section: Discussionsupporting
confidence: 83%
“…Most importantly, our conclusions are based on a relatively small number of female animals captured during a narrow time window. Previous studies in wild squirrel populations have shown that gut microbial communities differ between the sexes and vary seasonally (Ren et al, ). Thus, additional sampling from both sexes, along with dietary analysis, would help to more rigorously evaluate hypotheses that we propose.…”
Section: Discussionmentioning
confidence: 99%
“…; Ren et al . ). While genetic effects on the gut microbiota have been detected in laboratory and human studies (Wang et al .…”
Section: Introductionmentioning
confidence: 97%
“…When mice are cohoused, their microbiota composition converges (Hildebrand et al 2013;Seedorf et al 2014;Griffin et al 2017), and cohabiting, unrelated humans are more similar in their gut microbiota than those living apart (Song et al 2013). Strong environmental effects have also been reported in studies of wild animals, including seasonal and habitat differences (Maurice et al 2015;Amato et al 2016;Ren et al 2017). While genetic effects on the gut microbiota have been detected in laboratory and human studies (Wang et al 2018), these are often rather weak, and within-species studies typically emphasise the strong influence of environmental factors, such as diet (Carmody et al 2015;Rothschild et al 2018;Weissbrod et al 2018).…”
Section: Introductionmentioning
confidence: 99%